Social Responsibility Initiative Implementation in the Public Sector in Latvia - Voronchuk, Inesa; Stariņeca, Olga (Socialiniai tyrimai, 2014)
The public sector provides many different jobs in Latvia; however, the number of people employed in the public sector is small. Sometimes private sector organisations with a socially responsible culture are more attractive for specialists. The authors propose to evaluate Social Responsibility’s (SR) importance, benefits, and ways of possible implementation for several types of public sector organisations. The objective of this paper is to enquire what kind of activities organisations need to carry out to be included in the Sustainability Index rating and overview the possible reasons of difficulties encountered by public organisations. The authors describe the structure of the public sector and the Sustainability Index (SI) mechanism in Latvia and evaluate public organisations included in the SI rating by their activities directed to sustainable development; i.e., socially responsible (SR) activities.